Determinants of customer satisfaction on catering service in Electric Train Service (ETS), Keretapi Tanah Melayu Berhad (KTMB) / Izhar Hafifi Zainal Abidin... [et al.] - Zainal Abidin, Izhar Hafifi; Ab Ghani, Intan Suzaini; Mohd Amin, Nurizati; Usman, Samsul Bahri; Mohd Piah, Zul Hazam (UiTM Cawangan Johor, 2019)
In Malaysia, Electrified Train Services (ETS) is the first high speed intercity train system. ETS was executed under the Eighth and Ninth Malaysia Plan with the intention to enhance the operational efficiency and service of Keretapi Tanah Melayu Berhad (KTMB). This service provides an improved travel time for a long-haul journey. As a competitor to other means of public transportation such as airline, this ETS service must be constantly innovative to stay relevant. To maintain and improve this service, the underlying forces that affect customer satisfaction including catering service, needs to be understood. The purpose of this study is to identify the determinants of customer satisfaction on the catering service in ETS of KTMB and among the most common factor discussed are food quality, service quality and atmosphere. 180 questionnaires were distributed to passengers who buy meals at the ETS cabin café and a total of 104 questionnaires were returned. Descriptive analysis was first conducted to examine the demographic characteristics of the respondents. Multiple linear regression analysis was then performed to determine the relationship among variables. The findings of this study clearly show that there were positive relationships between food quality and atmosphere with customers' satisfaction in a surprising manner, no significant relationship between service quality and customers' satisfaction discovered. Among the two significant factors, the food quality has the strongest influence on customers' satisfaction. Therefore, it is necessary for the ETS catering to continuously understand customers' need especially with regards to food quality. Improving customers' satisfaction will lead to the development of customer relationship, revenue increase and stronger competitive advantage.